Pengaruh Waktu Pemanasan Sebelum Inkubasi Terhadap Kualitas Telur Tetas Ayam Buras - Nining Haryuni; M. Fathoali; Anna Lidyawati; - Lestariningsih (LPPM Universitas Nahdlatul Ulama Blitar, 2022)
The purpose of this study was to determine the effect of heating before incubation on the quality of native chicken hatching eggs. This study used 200 eggs from native chickens. This research is a laboratory research using Completely Randomized Design (CRD) with 4 treatments and 5 replications. Each treatment used 10 hatching eggs. If statistical analysis shows a significantly different or very significant effect, it will be continued by using Duncan's test. In this study, the results showed that heating of hatching eggs before incubation had a very significant effect (p<0.01) on fertility and hatchability, but had an insignificant effect (p>0.05) on weight loss of hatching eggs. The average egg weight loss in this study ranged from 0.00-0.10%, fertility 70.94-83.15%, embrio mortality 15-40% and hatchability ranged from 60-85%. Based on the results of the study, it can be concluded that the heating of the hatching eggs before the eggs are put into the incubator can reduce the quality of the hatching eggs. The longer heating time causes the lower quality of hatching eggs.